1998
DOI: 10.1029/98wr01282
|View full text |Cite
|
Sign up to set email alerts
|

Effect of groundwater springs on NO3 concentrations during summer in Catskill Mountain streams

Abstract: Abstract.Groundwater and stream water data collected at three headwater catchments in the Neversink River watershed indicate that base flow is sustained by groundwater from two sources: a shallow flow system within the till and soil and a deep flow system within bedrock fractures and bedding planes that discharges as perennial springs. Data from eight wells finished near the till/bedrock interface indicate that saturated conditions are not maintained in the shallow flow system during most summers. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
167
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(186 citation statements)
references
References 38 publications
14
167
5
Order By: Relevance
“…High concentrations in upland tension lysimeters which occur only during the dormant season have not been observed at the groundwater seep. The seep remained near background levels (0.02 mg/L) throughout the growing season, unlike groundwater seeps in the Catskills Mountains in New York, USA, that showed higher summer concentrations that were linked to atmospheric deposition recharged during winter [Burns et al, 1998]. This suggests that a lagged transport of atmospheric deposition at Pond Branch (mechanism #1) is highly unlikely.…”
Section: Assessing Multiple Alternative Hypothesesmentioning
confidence: 95%
“…High concentrations in upland tension lysimeters which occur only during the dormant season have not been observed at the groundwater seep. The seep remained near background levels (0.02 mg/L) throughout the growing season, unlike groundwater seeps in the Catskills Mountains in New York, USA, that showed higher summer concentrations that were linked to atmospheric deposition recharged during winter [Burns et al, 1998]. This suggests that a lagged transport of atmospheric deposition at Pond Branch (mechanism #1) is highly unlikely.…”
Section: Assessing Multiple Alternative Hypothesesmentioning
confidence: 95%
“…Those studies all focused on headwater catchments and catchments that were much smaller in area (0.02-0.26 ha) than the KEW (5.99 ha). Many studies have indicated an important contribution of bedrock groundwater to storm-runoff generation [e.g., Terajima and Moroto, 1990;Wilson et al, 1993] and to base-flow discharge [e.g., Mulholland, 1993;Burns et al, 1998]. The KEW is a watershed that includes several headwater catchments.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate export from diffuse sources (Burns et al, 1998;Boesch et al, 2001;Rabalais, 2002;De Vries et al, 2003) is a major cause of eutrophication and episodic acidification for inland aquatic systems and coastal zones (Vitousek et al, 1997;Crimo and McDonnell, 1997;Creed and Band, 1998;Galloway et al, 2003;Meader and Goldstein, 2003;Wellington and Driscoll, 2004). Resolving nutrient leaching rates of various diffuse sources may help watershed sustainability management maintaining required water quality and maximizing agricultural activity for food production.…”
Section: Introductionmentioning
confidence: 99%